Composition for sealing electronic device, film for sealing electronic device, and method for forming film for sealing electronic device

By using a composition of a specific photopolymerizable monomer and a photopolymerization initiator, the problems of appearance and luminous efficiency of the organic light emitting element in a bent state are solved, and the dielectric constant is reduced.

CN119923981APending Publication Date: 2025-05-02KONICA MINOLTA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380057085.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-26
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has problems with appearance and reduced luminous efficiency in the organic light emitting element package in the bending state, and the relative dielectric constant is relatively high.

Method used

By using an electronic device packaging composition containing (meth)acrylate as a photopolymerizable monomer, the packaging film formed is cured by irradiating 395 nm ultraviolet rays with 1.5 J/cm−2 under a nitrogen environment, the refractive index of the packaging film is in the range of 1.45 to 1.56 and the extinction coefficient is in the range of 50×10−5 to 200×10−5.

Benefits of technology

The reliability test in the bending state has a good appearance, excellent luminous efficiency, and a lower relative dielectric constant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259409110000121
    Figure BDA0005259409110000121
  • Figure BDA0005259409110000122
    Figure BDA0005259409110000122
  • Figure BDA0005259409110000141
    Figure BDA0005259409110000141
Patent Text Reader

Abstract

This composition for encapsulating an electronic device contains a photopolymerizable monomer and a photopolymerization initiator, contains a (meth) acrylate as the photopolymerizable monomer, and when the composition is cured by irradiation with ultraviolet light having a wavelength of 395 nm at 1.5 Jcm <-2 > in a nitrogen atmosphere, the refractive index at a wavelength of 380 nm of a formed electronic device encapsulating film is in the range of 1.45-1.56, and the refractive index at a wavelength of 380 nm is in the range of 1.45-1.56. And the extinction coefficient of the electronic device sealing film at the wavelength of 380 nm is in the range of 50 * 10 <-5 > to 200 * 10 <-5 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for encapsulating electronic devices, an electronic device encapsulating film and a method for forming an electronic device encapsulating film, and in particular to a composition for encapsulating electronic devices that can obtain a encapsulating film that has good appearance after a reliability test in a bent state, excellent luminous efficiency after a bending reliability test, and a low relative dielectric constant. Background Art

[0002] For electronic devices, particularly organic electroluminescent devices (hereinafter also referred to as "organic EL devices" or "organic EL elements"), it has been proposed to cover the surface of the organic EL element with an encapsulation layer to prevent the organic materials and electrodes used from being degraded by moisture.

[0003] As a technology for encapsulating organic EL elements, for example, the technology described in Patent Document 1 discloses a composition for encapsulating an organic light-emitting element, which comprises a photopolymerizable (photocurable) monomer and an initiator, wherein the photopolymerizable monomer does not contain a silicon-based photopolymerizable monomer but comprises a specific monomer containing an aromatic group and a monomer containing a non-aromatic group. It is believed that this technology can provide a composition for encapsulating an organic light-emitting element having a high refractive index and a high curing rate, excellent diffusibility, and a low plasma etching rate after curing.

[0004] However, in the technology described in Patent Document 1, when the organic light emitting element is folded, creases are generated after a reliability test, which causes a problem in appearance.

[0005] In addition, there is a problem that the luminous efficiency is reduced when the organic light emitting element is bent.

[0006] Furthermore, it is preferred that the material is not easily polarized when an electric field is applied to the electronic device, and that the relative dielectric constant is low.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2020-198304 Summary of the invention

[0010] The present invention is made in view of the above problems and circumstances, and the problem to be solved is to provide a composition for encapsulating electronic devices that can obtain an encapsulating film having good appearance after a reliability test in a bent state, excellent luminous efficiency after a bending reliability test, and low relative dielectric constant. In addition, an electronic device encapsulating film using the composition for encapsulating electronic devices and a method for forming the same are provided.

[0011] In order to solve the above-mentioned problems, the inventors have studied the causes of the above-mentioned problems and found that by containing (meth)acrylate as a photopolymerizable monomer and making the refractive index and extinction coefficient of the packaging film cured by irradiation under specific environmental conditions within a specific range, a packaging film with excellent appearance and luminous efficiency after reliability testing in a bent state and a low relative dielectric constant can be obtained, thereby completing the present invention.

[0012] That is, the above-mentioned problems of the present invention are solved by the following means.

[0013] 1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator,

[0014] The composition for encapsulating electronic devices contains (meth)acrylate as a photopolymerizable monomer.

[0015] In nitrogen environment, 1.5 J cm -2 When cured by irradiation with ultraviolet light of wavelength 395 nm, the refractive index of the formed electronic device packaging film at wavelength 380 nm is in the range of 1.45 to 1.56, and the extinction coefficient of the electronic device packaging film at wavelength 380 nm is within the range of 50×10 -5 ~200×10 -5 within the range.

[0016] 2. The composition for encapsulating electronic components according to item 1, wherein the refractive index is within a range of 1.50 to 1.53.

[0017] 3. The composition for encapsulating electronic devices according to item 1, wherein the extinction coefficient is 125×10 -5 ~200×10 -5 within the range.

[0018] 4. The composition for encapsulating electronic components according to item 1, wherein the refractive index n and the extinction coefficient k satisfy the following relationship.

[0019] k / n≥100×10 -5

[0020] 5. The composition for encapsulating an electronic device according to item 1, wherein the photopolymerizable monomer contained in the composition for encapsulating an electronic device has an average double bond number of 5 or less.

[0021] 6. The composition for electronic device encapsulation according to item 1, wherein energy levels of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the photopolymerizable monomer contained in the composition for electronic device encapsulation satisfy the following relationship.

[0022] 5.9eV≤LUMO-HOMO≤6.5eV

[0023] 7. An electronic device encapsulating film, which is an electronic device encapsulating film obtained by encapsulating an electronic device by curing a composition for encapsulating an electronic device containing a photopolymerizable monomer and a photopolymerization initiator,

[0024] The electronic device packaging film contains (meth)acrylate as the photopolymerizable monomer.

[0025] The refractive index of the electronic device packaging film at a wavelength of 380 nm is in the range of 1.45 to 1.56, and

[0026] The extinction coefficient of the above-mentioned electronic device packaging film at a wavelength of 380nm is 50×10 -5 ~200×10 -5 within the range.

[0027] 8. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having:

[0028] The first encapsulation layer comprises silicon nitride, silicon oxide or silicon oxynitride, and

[0029] The second encapsulating layer uses the composition for encapsulating an electronic device according to any one of items 1 to 6.

[0030] 9. The electronic device encapsulation film according to item 8, further comprising a third encapsulation layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulation layer.

[0031] 10. A method for forming an electronic device encapsulating film, comprising forming an electronic device encapsulating film using the composition for encapsulating an electronic device according to any one of items 1 to 6, the method comprising:

[0032] The process of forming a first encapsulation layer on the electronic device by a vapor phase method, and

[0033] A step of forming a second encapsulating layer by applying the electronic component encapsulating composition onto the first encapsulating layer.

[0034] 11. The method for forming an electronic device encapsulation film according to item 10, further comprising the step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.

[0035] 12. The method for forming an electronic device encapsulation film according to item 10, wherein the second encapsulation layer is formed by an inkjet method.

[0036] According to the above method of the present invention, a composition for encapsulating electronic devices can be provided, which can obtain an encapsulating film having good appearance after a reliability test in a folded state, excellent luminous efficiency after a folded reliability test, and low relative dielectric constant. In addition, an electronic device encapsulating film obtained by using the composition for encapsulating electronic devices and a method for forming the same are provided.

[0037] The mechanism of effect or action of the present invention is not clear, but is presumed as follows.

[0038] (Appearance after reliability test in a bent state)

[0039] When conducting reliability tests in a folded state, creep occurs due to the bending stress applied over a long period of time, causing deformation of the cured film. This deformation causes changes in the optical path length, and changes in the appearance after the reliability test.

[0040] In the present invention, by making the refractive index of the packaging film and the extinction coefficient as a measure of the absorbed light within the above-mentioned specific range, the optical appearance is less likely to change due to deformation in the bent state due to the balance between the refraction and absorption of light. That is, the optical path length is shortened due to the low refractive index, so the change in the optical path length before and after the reliability test in the bent state is reduced, and the amount of reflected light from the outside is reduced due to the absorption of light, so that the crease after the reliability test in the bent state can be suppressed and the appearance can be improved.

[0041] (Luminous efficiency after bending reliability test)

[0042] Repeated bending reliability tests may cause deformation and cracks in the cured film. If the cured film is deformed or has tiny cracks, the emission mode of light from the light-emitting element will change. In other words, there is a concern that if it is deformed, the light will be emitted laterally due to the change in optical path length and refraction of light, and if cracks are generated, the light will not be emitted due to the difference in refractive index between the air in the gap and the crack.

[0043] Therefore, it is presumed that in the present invention, by setting the refractive index of the packaging film to the above-mentioned specific range, the refraction of light can be suppressed, the refractive index difference with the air layer in the microcrack can be suppressed, and high luminous efficiency can be maintained even in the bent state.

[0044] (Relative dielectric constant)

[0045] What is even more surprising is that when the refractive index of the encapsulation film and the extinction coefficient, which is a measure of absorbed light, are within the above-mentioned specific range, the relative dielectric constant becomes low. The mechanism of action is not yet clear, but it is believed that by being within the specific range, the energy gap becomes larger and electron transition is less likely to occur. The dielectric constant depends on electron polarization. It is believed that electron polarization occurs due to the distribution of electrons caused by the disturbance of the electric field, but it is difficult to produce a large electron distribution because electron transition is less likely to occur. DETAILED DESCRIPTION

[0046] The composition for encapsulating electronic devices of the present invention comprises a photopolymerizable monomer and a photopolymerization initiator. The composition for encapsulating electronic devices comprises a (meth)acrylate as a photopolymerizable monomer. -2 When cured by irradiation with ultraviolet light of wavelength 395 nm, the refractive index of the formed electronic device packaging film at wavelength 380 nm is in the range of 1.45 to 1.56, and the extinction coefficient of the electronic device packaging film at wavelength 380 nm is within the range of 50×10 -5 ~200×10 -5 within the range.

[0047] This feature is a technical feature common to or corresponding to the following embodiments.

[0048] As an embodiment of the present invention, in terms of appearance and luminous efficiency after a reliability test in a bent state, it is more preferable that the refractive index is in the range of 1.50 to 1.53, and the extinction coefficient is in the range of 125×10 -5 ~200×10 -5 within the range.

[0049] In terms of appearance after the reliability test in the bent state and luminous efficiency after the bending reliability test, it is preferred that the refractive index n and the extinction coefficient k satisfy k / n ≥ 100×10 -5 relationship.

[0050] The photopolymerizable monomer contained in the composition for encapsulating an electronic device preferably has an average double bond number of 5 or less in terms of appearance after a reliability test in a folded state and luminous efficiency after a folded reliability test.

[0051] In addition, in terms of appearance after a reliability test in a bent state, luminous efficiency after a bending reliability test, and relative dielectric constant, it is preferred that the energy levels of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the photopolymerizable monomer contained in the electronic device encapsulation composition satisfy the following relationship:

[0052] 5.9eV≤LUMO-HOMO≤6.5eV.

[0053] An electronic device encapsulation film according to one embodiment of the present invention is obtained by curing an electronic device encapsulation composition containing a photopolymerizable monomer and a photopolymerization initiator to encapsulate an electronic device. The electronic device encapsulation film contains a (meth)acrylate as the photopolymerizable monomer. The refractive index of the electronic device encapsulation film at a wavelength of 380 nm is in the range of 1.45 to 1.56, and the extinction coefficient of the electronic device encapsulation film at a wavelength of 380 nm is in the range of 50×10 -5 ~200×10 -5 within the range.

[0054] Thus, it is possible to manufacture an electronic device packaging film having good appearance after a reliability test in a folded state, excellent luminous efficiency after a folded reliability test, and a low relative dielectric constant.

[0055] An electronic device encapsulating film according to another aspect of the present invention encapsulates an electronic device, and includes a first encapsulating layer containing silicon nitride, silicon oxide, or silicon oxynitride, and a second encapsulating layer formed using the electronic device encapsulating composition.

[0056] Thus, it is possible to manufacture an electronic device packaging film having good appearance after a reliability test in a folded state, excellent luminous efficiency after a folded reliability test, and a low relative dielectric constant.

[0057] In terms of excellent sealing performance, it is preferred that a third sealing layer containing silicon nitride, silicon oxide, or silicon oxynitride is provided on the second sealing layer.

[0058] The method for forming an electronic device encapsulating film of the present invention forms an encapsulating film using the above-mentioned electronic device encapsulating composition, and comprises: a step of forming a first encapsulating layer on an electronic device by a vapor phase method, and a step of forming a second encapsulating layer by coating the above-mentioned electronic device encapsulating composition on the above-mentioned first encapsulating layer.

[0059] Thus, it is possible to form an electronic device packaging film having good appearance after a reliability test in a folded state and excellent light emission efficiency after a folded reliability test.

[0060] In terms of excellent sealing performance, it is preferable to include a step of forming a third sealing layer on the second sealing layer by a vapor phase method.

[0061] In addition, it is preferable to use an inkjet method in the step of forming the second sealing layer because the layer can be formed with high precision.

[0062] Hereinafter, the present invention and its constituent elements and forms and modes for carrying out the present invention will be described. It should be noted that in the present application, "to" is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0063] [Overview of the composition for encapsulating electronic devices of the present invention]

[0064] The composition for encapsulating an electronic device of the present invention (hereinafter, also referred to as "encapsulating composition") is a composition for encapsulating an electronic device containing a photopolymerizable monomer and a photopolymerization initiator, containing a (meth)acrylate as a photopolymerizable monomer, and having a photopolymerizable monomer of 1.5 Jcm -2 When cured by irradiation with ultraviolet light of a wavelength of 395 nm, the formed electronic device packaging film (hereinafter, also referred to as "packaging film") has a refractive index of 1.45 to 1.56 at a wavelength of 380 nm, and an extinction coefficient of 50×10 -5 ~200×10 -5 within the range.

[0065] <Refractive Index>

[0066] The encapsulation composition of the present invention is heated to 1.5 Jcm in a nitrogen environment. -2 When cured by irradiation with ultraviolet light having a wavelength of 395 nm, the refractive index of the formed encapsulating film at a wavelength of 380 nm is in the range of 1.45 to 1.56, more preferably in the range of 1.50 to 1.53.

[0067] The refractive index is determined using a spectroscopic ellipsometer (UVSEL / FUV-FGMS, manufactured by HORIBA JYOBIN-YVON CO., LTD.) Specifically, the refractive index at 250 nm to 800 nm is measured, and the refractive index n at 380 nm is determined.

[0068] Examples of methods for adjusting the refractive index to be within the range of 1.45 to 1.56 include, but are not limited to, using a monomer structure having a small number of heteroatoms, an alicyclic hydrocarbon structure, or a chain hydrocarbon structure.

[0069] Specific examples of the structure of the alicyclic hydrocarbon include, but are not limited to, alicyclic (meth)acrylates such as isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and cyclohexyl (meth)acrylate; and alicyclic (meth)acrylates such as 1,3-adamantanediol di(meth)acrylate, 1,3-adamantanedimethanol di(meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 3-hydroxy-1-adamantyl (meth)acrylate, 1-adamantyl (meth)acrylate, and tricyclodecane dimethanol (meth)acrylate.

[0070] Examples of the structure of the chain hydrocarbon include, but are not limited to, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,11-undecanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 2-ethylhexyl (meth)acrylate, isostearyl (meth)acrylate, lauryl (meth)acrylate, hexyl (meth)acrylate, and isodecyl (meth)acrylate. In addition, particles having a desired refractive index may be added within a range that does not impair the ejectability of the inkjet.

[0071] The refractive index of the photopolymerizable monomer constituting the encapsulating composition can be determined using an Abbe refractometer, and is preferably 1.43 to 1.50 as the refractive index of the D line at 25°C (nd25).

[0072] <Extinction coefficient>

[0073] The encapsulation composition of the present invention is heated to 1.5 Jcm in a nitrogen environment. -2 When cured by irradiation with ultraviolet light at a wavelength of 395 nm, the extinction coefficient of the formed packaging film at a wavelength of 380 nm is 50×10 -5 ~200×10 -5 More preferably, it is within the range of 125×10 -5 ~200×10 -5 within the range.

[0074] The extinction coefficient is determined similarly to the refractive index using a spectroscopic ellipsometer (UVSEL / FUV-FGMS, manufactured by HORIBA JYOBIN-YVON CO., LTD.) Specifically, the extinction coefficient at 250 nm to 800 nm is measured, and the extinction coefficient k at 380 nm is determined.

[0075] As for making the above extinction coefficient 50×10 -5 ~200×10 -5 The method within the range of can be cited, for example, a structure with few heteroatoms, a structure with few aromatic hydrocarbons, a structure with few multiple bonds in the structure of the monomer. In addition, it can be cited that a pigment is added within the range that does not damage the luminescent properties of the organic EL.

[0076] In terms of appearance after a reliability test in a folded state and luminous efficiency after a folded reliability test, it is preferable that the refractive index n and the extinction coefficient k satisfy the following relationship.

[0077] k / n≥100×10 -5

[0078] [Composition of the composition for encapsulating electronic devices]

[0079] The composition for encapsulating electronic components of the present invention contains a photopolymerizable monomer and a photopolymerization initiator.

[0080] As the photopolymerizable monomer, a (meth)acrylate is contained.

[0081] In the present specification, "(meth)acrylate" means at least one of acrylate and methacrylate.

[0082] In addition, the "electronic device" in the present invention refers to an element that generates, amplifies, converts or controls electrical signals by using the kinetic energy and potential energy of electrons. Examples include active elements such as light emitting diode elements, organic electroluminescent elements, photoelectric conversion elements and transistors. In addition, in the present invention, passive elements such as resistors and capacitors that passively work by "impeding" or "accumulating" the action of other elements are also included in the electronic device.

[0083] Therefore, the encapsulating composition of the present invention is used to form an encapsulating film for encapsulating the above-mentioned electronic device.

[0084] <Photopolymerizable monomer>

[0085] The “photopolymerizable monomer” refers to a photopolymerizable monomer (also referred to as a “photocurable monomer”) that can undergo a polymerization (curing) reaction by absorbing light by itself or a photopolymerization initiator to generate active ions or radicals.

[0086] As the photopolymerizable monomer, a non-silicon monomer that does not contain silicon (Si) can be used, for example, a monomer consisting of only elements selected from C, H, O, N or S, but not limited thereto. The photopolymerizable monomer can be synthesized using a conventional synthesis method or purchased from a commercial product.

[0087] As the above-mentioned photopolymerizable monomer, there can be mentioned the following photopolymerizable monomer (A) without an aromatic hydrocarbon group, the photopolymerizable monomer (B) with an aromatic hydrocarbon group, etc. As described above, when making a packaging film, it is appropriately selected from these photopolymerizable monomers in a manner such that the above-mentioned refractive index and extinction coefficient satisfy the above-mentioned range.

[0088] (Average number of double bonds)

[0089] The photopolymerizable monomer contained in the composition for encapsulating an electronic device of the present invention preferably has an average double bond number of 5 or less in terms of appearance after a reliability test in a folded state and luminous efficiency after a folded reliability test.

[0090] The average number of double bonds can be calculated as follows using the mass ratio w of each monomer when the number of double bonds contained in each monomer is defined as d and the total mass of all monomers is defined as 1.

[0091] Average number of double bonds = d1×w1+d2×w2+···

[0092] (The subscripts d and w indicate the monomer numbers.)

[0093] (HOMO and LUMO energy levels)

[0094] In terms of appearance after the reliability test in the bent state, luminous efficiency after the bending reliability test, and relative dielectric constant, it is preferred that the average value of the energy level of the highest occupied molecular orbital (HOMO) and the average value of the energy level of the lowest unoccupied molecular orbital (LUMO) of the above-mentioned photopolymerizable monomer contained in the encapsulation composition of the present invention satisfy the following relationship.

[0095] 5.9eV≤LUMO-HOMO≤6.5eV

[0096] Here, the average value of the energy level of the highest occupied molecular orbital (HOMO) and the average value of the energy level of the lowest unoccupied molecular orbital (LUMO) are calculated by the following formulas.

[0097] Average value of HOMO = HOMO1×w1+HOMO2×w2+...

[0098] Average value of LUMO = LUMO1×w1+LUMO2×w2+...

[0099] In the above formula, w represents the mass ratio of each monomer described above. In addition, the subscripts of w, HOMO and LUMO represent the numbers of the monomers.

[0100] HOMO and LUMO can be calculated using chemical structure information computer software. Examples of the calculation software include quantum chemical calculation programs "Gaussian series" manufactured by HULINKS Corporation.

[0101] The average value of the HOMO and the average value of the LUMO are calculated from the values ​​of HOMO and LUMO of each monomer obtained using the software, and the energy gap (Gap) between the average values ​​of the HOMO and the average values ​​of the LUMO is calculated. In the calculation, B3LYP is used as the functional.

[0102] Gap (unit: eV) = average value of LUMO - average value of HOMO

[0103] Examples of a method for making the above Gap 5.9 eV≤LUMO-HOMO≤6.5 eV include using a structure having a small number of heteroatoms, an alicyclic hydrocarbon structure, a chain hydrocarbon structure, and the like in the structure of a monomer.

[0104] <Photopolymerizable monomer (A) not having an aromatic hydrocarbon group>

[0105] The above-mentioned photopolymerizable monomer (A) not having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (A)") does not contain an aromatic hydrocarbon group, and may contain a monomer having 1 to 20, specifically 1 to 6, one or more selected from vinyl, acrylic and methacrylic groups as photocurable functional groups (photopolymerizable functional groups), for example, it may contain 1 to 3, 1 to 2, 1 or 2.

[0106] In the present invention, the weight average molecular weight of the photopolymerizable monomer (A) may be in the range of 100 to 500 g / mol, 130 to 400 g / mol, or 200 to 300 g / mol. By keeping the weight average molecular weight of the monomer within the range, a more favorable effect can be exhibited in the process.

[0107] The photopolymerizable monomer (A) may include a monofunctional monomer or a polyfunctional monomer having a photocurable functional group, or a mixture thereof.

[0108] Specifically, the above-mentioned photopolymerizable monomer (A) can be a (meth)acrylate monomer, which can be an unsaturated carboxylic acid ester having an alkyl group with 1 to 20 carbon atoms, a cycloalkyl group with 3 to 20 carbon atoms, a hydroxyl group and an alkyl group with 1 to 20 carbon atoms; an unsaturated carboxylic acid ester having an aminoalkyl group with 1 to 20 carbon atoms; a vinyl ester of a saturated or unsaturated carboxylic acid with 1 to 20 carbon atoms; a cyanide vinyl compound; an unsaturated amide compound; a monofunctional or polyfunctional (meth)acrylate of a monohydric alcohol or a polyhydric alcohol, etc.

[0109] The above-mentioned "polyol" is an alcohol having two or more hydroxyl groups, and can refer to an alcohol having 2 to 20, preferably 2 to 10, more preferably 2 to 6 hydroxyl groups.

[0110] In one example, the (meth)acrylate monomer having no aromatic hydrocarbon group in the photopolymerizable monomer (A) may be a mono(meth)acrylate, a di(meth)acrylate, a tri(meth)acrylate, a tetra(meth)acrylate, or the like having a substituted or unsubstituted C1-C20 (carbon number 1-20) alkyl group, a substituted or unsubstituted C1-C20 alkylsilyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C1-C20 alkylene group, an amine group, an oxirane group, or the like.

[0111] Specifically, the (meth)acrylate monomers without an aromatic hydrocarbon group may include: unsaturated carboxylic acid esters of (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, and cyclohexyl (meth)acrylate; unsaturated carboxylic acid aminoalkyl esters such as 2-aminoethyl (meth)acrylate and 2-dimethylaminoethyl (meth)acrylate; saturated or unsaturated carboxylic acid vinyl esters such as vinyl acetate; cyanide vinyl compounds such as (meth)acrylonitrile; unsaturated amide compounds such as (meth)acrylamide; ethylene glycol di(meth)acrylate )acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate or a mixture thereof, but is not limited thereto.

[0112] In one example of the present invention, the photopolymerizable monomer (A) may be a non-aromatic monomer containing no aromatic group and may include at least any one of a mono(meth)acrylate having an alkyl group having 1 to 20 carbon atoms, a mono(meth)acrylate having an amine group, a di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a di(meth)acrylate having an ethylene oxide group, a tri(meth)acrylate having an ethylene oxide group, and a mono(meth)acrylate and a di(meth)acrylate having a cyclic hydrocarbon alkyl group.

[0113] The mono(meth)acrylate having a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms may specifically be decyl(meth)acrylate, undecyl(meth)acrylate, lauryl(meth)acrylate, tridecyl(meth)acrylate, tetradecyl(meth)acrylate, pentadecyl(meth)acrylate, hexadecyl(meth)acrylate, heptadecyl(meth)acrylate, octadecyl(meth)acrylate, nonadecyl(meth)acrylate, eicosyl(meth)acrylate or a mixture thereof, but is not limited thereto.

[0114] The mono(meth)acrylate having an amine group may be 2-aminoethyl(meth)acrylate, 2-dimethylaminoethyl(meth)acrylate, or a mixture thereof, but is not limited thereto.

[0115] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, a di(meth)acrylate having an alkylene group having 1 to 20 carbon atoms, or a non-silicon-based di(meth)acrylate containing a substituted or unsubstituted long-chain alkylene group.

[0116] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate or a mixture thereof, but is not limited thereto.

[0117] When the (meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms is contained, the photocuring rate of the encapsulating composition of the present invention is further improved, and the viscosity can be reduced.

[0118] The di(meth)acrylate or tri(meth)acrylate having an ethylene oxide group may specifically be ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, or a mixture thereof, but is not limited thereto.

[0119] The mono(meth)acrylate and di(meth)acrylate having a cyclic hydrocarbon alkyl group may specifically be isobornyl(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, and dicyclopentenyl(meth)acrylate, but are not limited thereto.

[0120] The photopolymerizable monomer (A) is preferably contained in an amount of 55 to 95% by mass, more preferably 60 to 90% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). By being within the above range, the viscosity of the encapsulating composition of the present invention is suitable for forming an encapsulating film for electronic devices.

[0121] <Photopolymerizable monomer (B) having an aromatic hydrocarbon group>

[0122] The above-mentioned photopolymerizable monomer (B) having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (B)") has a structure represented by the following general formula (1) and contains two or more phenyl groups and hetero atoms, and the above-mentioned photopolymerizable monomer (B) contains at least mono(meth)acrylate or di(meth)acrylate.

[0123] General formula (1)

[0124]

[0125] [In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups. 1 and Z 2 Each independently has a structure represented by the following general formula (2). a and b are each an integer of 0 to 2, and a+b is an integer of 1 to 4.]

[0126] General formula (2)

[0127]

[0128] [In the above general formula (2), * is a linking portion to the carbon of P. X represents a single bond, O or S. Y represents a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms. R 1 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. c is an integer of 0 or 1.]

[0129] In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0130] The above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a hydrocarbon group formed by connecting the two or more substituted or unsubstituted phenyl groups by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group when the two or more substituted or unsubstituted phenyl groups are not condensed.

[0131] For example, the hydrocarbon group containing two or more phenyl groups or the heteroatom-containing hydrocarbon group containing two or more phenyl groups may include a substituted or unsubstituted biphenyl group, a substituted or unsubstituted triphenylmethyl group, a substituted or unsubstituted terphenyl group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted terphenylene group, a substituted or unsubstituted quaterphenylene group, a substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl group, a substituted or unsubstituted 2,2-diphenylpropyl group, a substituted or unsubstituted diphenylmethyl group, a substituted or unsubstituted cumylphenyl group, a substituted or unsubstituted bisphenol F group, a substituted or unsubstituted bisphenol A group, a substituted or unsubstituted biphenyloxy group, a substituted or unsubstituted terphenyloxy group, a substituted or unsubstituted quaterphenyloxy group, a substituted or unsubstituted pentphenyloxy group, and structural isomers thereof, but are not limited thereto.

[0132] The monomer having two or more substituted or unsubstituted phenyl groups may be a mono(meth)acrylate, a di(meth)acrylate or a mixture thereof, and examples thereof include 4-(meth)acryloyloxy-2-hydroxybenzophenone, 3,3-diphenylethyl(meth)acrylate, benzoyloxyphenyl(meth)acrylate, bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, 4-cumylphenoxyethyl acrylate, ethoxylated bisphenylfluorene diacrylate, 2-phenylphenoxyethyl(meth)acrylate, 2,2'-phenylphenoxyethyl di(meth)acrylate, 2-phenylphenoxypropyl(meth)acrylate, 2,2'-phenylphenoxypropyldi(meth)acrylate, 2-phenylphenoxybutyl(meth)acrylate, 2,2'-phenylphenoxybutyldi(meth)acrylate, 2-( 2-(3-phenylphenyl)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 2-phenyl-2-(phenylthio)ethyl (meth)acrylate, 2-(triphenylmethoxy)ethyl (meth)acrylate, 4-(triphenylmethoxy)butyl (meth)acrylate, 3-(biphenyl-2-yloxy)butyl (meth)acrylate, 2-(biphenyl-2-yloxy)butyl (meth)acrylate, 4-(biphenyl-2-yloxy)propyl (meth)acrylate, acrylate, 3-(biphenyl-2-yloxy)propyl (meth)acrylate, 2-(biphenyl-2-yloxy)propyl (meth)acrylate, 4-(biphenyl-2-yloxy)ethyl (meth)acrylate, 3-(biphenyl-2-yloxy)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 4,4'-bis(acryloyloxymethyl)biphenyl, 2,2'-bis(2-acryloyloxyethoxy)biphenyl, structural isomers thereof, or mixtures thereof, but are not limited thereto.

[0133] In addition, the (meth)acrylate mentioned in the present invention is just an example and is not limited to this.

[0134] In addition, the present invention includes all acrylates in a structural isomer relationship. For example, even if only 2,2'-phenylphenoxyethyl di(meth)acrylate is mentioned as an example of the present invention, the present invention also includes all 3,2'-phenylphenoxyethyl di(meth)acrylate, 3,3'-phenylphenoxyethyl di(meth)acrylate, etc. corresponding to the structural isomer.

[0135] In one example of the present invention, the monomer having two or more phenyl groups may be a mono(meth)acrylate represented by the following general formula (4).

[0136] General formula (4)

[0137]

[0138] In the above general formula (4), R 2 is hydrogen or methyl, R 3 is a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, R 4 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0139] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a hydrocarbon group formed by connecting the two or more substituted or unsubstituted phenyl groups by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group when the two or more substituted or unsubstituted phenyl groups are not condensed.

[0140] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups may include a substituted or unsubstituted biphenyl group, a substituted or unsubstituted triphenylmethyl group, a substituted or unsubstituted terphenyl group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted terphenylene group, a substituted or unsubstituted quaterphenylene group, a substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl group, a substituted or unsubstituted 2,2-diphenylpropyl group, a substituted or unsubstituted diphenylmethyl group, a substituted or unsubstituted cumylphenyl group, a substituted or unsubstituted bisphenol F group, a substituted or unsubstituted bisphenol A group, a substituted or unsubstituted biphenyloxy group, a substituted or unsubstituted terphenyloxy group, a substituted or unsubstituted quaterphenyloxy group, a substituted or unsubstituted pentphenyloxy group, etc., but are not limited thereto.

[0141] In one example of the present invention, the monomer having two or more phenyl groups may be a di(meth)acrylate represented by the following general formula (5).

[0142] General formula (5)

[0143]

[0144] In the above general formula (5), R 5 , R 9 are each independently hydrogen or methyl, R 6 , R 8 are each independently a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, 7 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0145] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a hydrocarbon group formed by connecting the two or more substituted or unsubstituted phenyl groups by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group when the two or more substituted or unsubstituted phenyl groups are not condensed.

[0146] For example, the hydrocarbon group may include substituted or unsubstituted biphenylene, substituted or unsubstituted triphenylmethylene, substituted or unsubstituted terphenylene, substituted or unsubstituted quaterphenylene, 2-phenyl-2-(phenylthio)ethylene, 2,2-diphenylpropylene, diphenylmethylene, etc., but is not limited thereto.

[0147] In the above general formula (1), a and b are integers of 0 to 2 respectively, and a+b is an integer of 1 to 4. In one example, a+b is an integer of 1 or 2.

[0148] The weight average molecular weight of the monomer having two or more substituted or unsubstituted phenyl groups is preferably in the range of 100 to 1000 g / mol, more preferably in the range of 130 to 700 g / mol, and particularly preferably in the range of 150 to 600 g / mol.

[0149] When the content is within the above range, a packaging film having a higher transmittance can be provided.

[0150] The photopolymerizable monomer (B) having an aromatic hydrocarbon group is preferably contained in an amount of 5 to 45% by mass, more preferably 10 to 40% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). By being within the above range, the viscosity is suitable for forming a packaging film.

[0151] In addition, specific examples of the photopolymerizable monomers (A) and (B) include the monomers listed in the examples described below in addition to the above monomers. Preferred combinations of the photopolymerizable monomers in the present invention are described in the examples described below.

[0152] <Photopolymerization initiator>

[0153] The photopolymerization initiator is not particularly limited as long as it is a common photopolymerization initiator capable of undergoing a photocurable reaction.

[0154] As the photopolymerization initiator, for example, a triazine-based, acetophenone-based, benzophenone-based, thioxanthone-based, benzoin-based, phosphorus-based, oxime-based, or a mixture thereof may be included.

[0155] The triazine initiator can be 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, s-triazine, 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl(piperonyl)-6-triazine, 2,4-(trichloromethyl(4'-methoxyphenylvinyl)-6-triazine or a mixture thereof.

[0156] The acetophenone-based initiator may be 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, and mixtures thereof.

[0157] The benzophenone-based initiator may be benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone or a mixture thereof.

[0158] The thioxanthone-based initiator may be thioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chlorothioxanthone or a mixture thereof.

[0159] The benzoin-based initiator may be benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzil dimethyl ketal or a mixture thereof.

[0160] The phosphorus-based initiator may be bisbenzoylphenylphosphine oxide, benzoyldiphenylphosphine oxide or a mixture thereof.

[0161] The oxime may be 2-(o-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione and 1-(o-acetoxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, or a mixture thereof.

[0162] The photopolymerization initiator is preferably contained in the encapsulation composition of the present invention in an amount of about 0.1 to 20 parts by mass relative to 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. By being within the above range, photopolymerization can be fully carried out during exposure, and a decrease in transmittance due to residual unreacted initiator after photopolymerization can be prevented.

[0163] Specifically, the photopolymerization initiator is preferably contained in an amount within a range of 0.5 to 10 parts by mass, more specifically 1 to 5 parts by mass.

[0164] In addition, the photopolymerization initiator is preferably contained in the encapsulating composition of the present invention in an amount of 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, based on the solid content. By being within the above range, photopolymerization can be sufficiently carried out and a decrease in transmittance due to residual unreacted initiator can be prevented.

[0165] In addition, carbazole-based, diketone-based, sulfonium-based, iodine-based Instead of the above-mentioned photopolymerization initiator, a photoacid generator or a photopolymerization initiator such as a photoacid generator, a diazo generator, or a biimidazole generator can be used.

[0166] <Other additives>

[0167] The encapsulation composition of the present invention may further contain other components including antioxidants, heat stabilizers, photosensitizers, dispersants, thermal crosslinking agents and surfactants within the range of obtaining the effects of the present invention. These components may be contained in the encapsulation composition of the present invention alone or in two or more combinations.

[0168] The above antioxidant can improve the thermal stability of the encapsulation layer. The antioxidant may include one or more selected from phenol, quinone, amine and phosphite, but is not limited thereto. For example, as an antioxidant, tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, tris(2,4-di-tert-butylphenyl)phosphite, etc. may be cited.

[0169] The antioxidant is preferably contained in the encapsulating composition in an amount of 0.01 to 3 parts by mass, more preferably 0.01 to 1 part by mass, based on 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. Within the above range, excellent thermal stability can be exhibited.

[0170] The heat stabilizer is contained in the encapsulating composition to suppress a change in viscosity of the encapsulating composition at room temperature, and any common heat stabilizer can be used without limitation.

[0171] For example, as the heat stabilizer, a sterically hindered phenolic heat stabilizer can be used, and specifically, poly(dicyclopentadiene-co-p-cresol), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylene-bis(4-methyl-6-tert-butylphenol), 6,6'-di-tert-butyl-2,2'-thiodi-p-cresol, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, triethylene glycol-bis(3-tert-butyl-4-hydroxy-5-methylphenyl), 4,4'-thiobis(6-tert-butyl-m-cresol), 3,3' The invention may be selected from the group consisting of: -bis(3,5-di-tert-butyl-4-hydroxyphenyl)-N,N'-hexamethylenebispropionamide, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), stearyl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, pentaerythritol tetrakis-1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(2-hydroxyethyl)isocyanurate-tris(3,5-di-tert-butylhydroxyphenylpropionate), but is not limited thereto.

[0172] The thermal stabilizer is contained in the encapsulating composition in an amount of 2000 ppm or less, preferably in a range of 0.01 to 2000 ppm, and more preferably in a range of 100 to 1000 ppm, based on the solid content relative to the total of the photopolymerizable monomer and the photopolymerization initiator. By being within the above range, the thermal stabilizer can further improve the storage stability and processability of the encapsulating composition in a liquid state.

[0173] The photosensitizer is a compound that has a function of transferring absorbed light energy to a photopolymerization initiator, and therefore can have the original photopolymerization initiator function even if the photopolymerization initiator used does not have absorption corresponding to light from a light source.

[0174] Examples of the photosensitizer include anthracene derivatives such as 9,10-dibutoxyanthracene; benzoin derivatives such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether;

[0175] Benzophenone derivatives such as benzoylbenzoic acid methyl ester, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propyleneoxy)ethyl]benzyl ammonium bromide, and (4-benzoylbenzyl)trimethylammonium chloride;

[0176] Thioxanthone derivatives such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one meso chloride; and other compounds. Among them, anthracene derivatives, benzoin derivatives, benzophenone derivatives, anthraquinone derivatives, and thioxanthone derivatives are preferably used.

[0177] <Ultraviolet curing>

[0178] As ultraviolet rays irradiated to cure the encapsulating composition of the present invention, a known method can be used, and there is no particular limitation as long as curing is performed by irradiating ultraviolet rays in the range of 200 to 400 nm. From the viewpoint of preventing degradation of electronic devices, it is preferred to use a 395 nm LED.

[0179] As long as the encapsulation composition is cured in an environment where ultraviolet rays are irradiated, a known method can be used, and there is no particular limitation as long as the curing is performed by irradiating ultraviolet rays. From the viewpoint of preventing degradation of electronic devices and preventing the influence of curing inhibition caused by oxygen, it is preferably irradiated in an inert gas environment. It is particularly preferred to irradiate under a nitrogen or argon atmosphere.

[0180] <Physical Properties>

[0181] From the viewpoint of further improving the ejection property from an inkjet head, the viscosity of the encapsulating composition of the present invention is preferably in the range of 3 to 30 mPa·s. From the viewpoint of further improving the ejection property from an inkjet head, the surface tension is preferably 15 mN / m or more and less than 45 mN / m.

[0182] The viscosity of the encapsulating composition of the present invention can be determined, for example, by measuring the temperature change of the dynamic viscoelasticity of the encapsulating composition using various rheometers.

[0183] In the present invention, these viscosities are values ​​obtained by the following method. The encapsulation composition of the present invention is placed in a stress-controlled rheometer Physica MCR300 (diameter of the vertebral plate: 75 mm, cone angle: 1.0°, manufactured by Anton Paar). Next, the encapsulation composition is heated to 100°C, and the encapsulation composition is cooled to 20°C under the conditions of a cooling rate of 0.1°C / s, a strain of 5%, and an angular frequency of 10 radian / s to obtain a temperature change curve of dynamic viscoelasticity.

[0184] The encapsulating composition of the present invention may contain pigment particles. When the encapsulating composition of the present invention contains a pigment, the average particle size of the pigment particles is within the range of 0.08 to 0.5 μm, and the maximum particle size is preferably within the range of 0.3 to 10 μm, from the viewpoint of further improving the ejection property from an inkjet head.

[0185] The average particle size of the pigment particles in the present invention refers to the value obtained by the dynamic light scattering method using a Zetasizer Nano ZSP manufactured by Malvern. It should be noted that the concentration of the encapsulating composition containing the coloring material is high and light is not transmitted in the measuring instrument, so the encapsulating composition is diluted 200 times before measurement. The measurement temperature is room temperature (25°C).

[0186] In addition, the sealing composition of the present invention is preferably selected from the density ρ, the surface tension σ of the sealing composition, the viscosity μ of the sealing composition, the nozzle diameter D, and the like in view of the ejection properties of the inkjet and the stabilization of the droplets during the flight of the ink. 0 The Ohnesorg number (Oh) represented by the following formula 1 is within the range of 0.1 to 1.

[0187]

[0188] The encapsulation composition of the present invention is preferably prepared to provide a cured polymer having a Tg (glass transition temperature) of 80° C. or higher in the film after polymerization. From the viewpoint of ensuring stability in the formation process, driving temperature, and reliability test of electronic devices, the Tg of the film after polymerization is preferably 80° C. or higher.

[0189] [Method for forming an electronic device packaging film]

[0190] The method for forming an electronic device packaging film of the present invention uses the above-mentioned electronic device packaging composition of the present invention to form a packaging film, and the method comprises: a step of forming a first packaging layer on an electronic device using a vapor phase method, and a step of forming a second packaging layer by coating the above-mentioned electronic device packaging composition on the above-mentioned first packaging layer.

[0191] In order to further improve the sealing performance of the electronic device, it is preferable to include a step of forming a third sealing layer on the second sealing layer by a vapor phase method.

[0192] <First sealing layer forming step>

[0193] The first encapsulation layer forming step forms a first encapsulation layer on the electronic device by a vapor phase method.

[0194] As gas phase methods, sputtering methods (for example, reactive sputtering methods including magnetron cathode sputtering, planar magnetron sputtering, dipole AC planar magnetron sputtering, dipole AC rotating magnetron sputtering, etc.), evaporation methods (for example, resistance heating evaporation, electron beam evaporation, ion beam evaporation, plasma assisted evaporation, etc.), thermal CVD method, catalytic chemical vapor deposition method (Cat-CVD), capacitive coupled plasma CVD method (CCP-CVD), optical CVD method, plasma CVD method (PECVD), epitaxial growth method, atomic layer deposition method (ALD) and other chemical evaporation methods can be cited. Among them, formation by ALD method and CVD method is preferred.

[0195] The first encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).

[0196] As a specific example of forming the first encapsulation layer, the following method can be cited: the pressure in the chamber is reduced in advance, silane (SiH 4 ), ammonia (NH 3 ), hydrogen (H 2 ) is formed by heating the raw material gas and then supplying it into the chamber.

[0197] The thickness of the first encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.

[0198] <Second Encapsulation Layer Formation Step>

[0199] The second encapsulating layer forming step forms the second encapsulating layer by applying the encapsulating composition of the present invention onto the first encapsulating layer.

[0200] Specifically, the method may include a step of coating the encapsulating composition on the first encapsulating layer (coating step), and subjecting the obtained coating film to a modification treatment by irradiating it with vacuum ultraviolet rays in a nitrogen atmosphere.

[0201] (Coating process)

[0202] As a coating method for the encapsulation composition, any appropriate method can be adopted, for example, spin coating, roll coating, flow coating, inkjet, spray coating, printing, dip coating, cast film forming, rod coating, gravure printing, etc. Among them, the inkjet method is preferably used in that the fine patterning required for encapsulating electronic devices such as organic EL elements can be performed as needed.

[0203] As the inkjet method, a known method can be used.

[0204] The inkjet method is roughly divided into two types: the drop-on-demand method and the continuous method, and either method can be used. As the drop-on-demand method, there are electro-mechanical conversion methods (such as single-chamber type, dual-chamber type, curved type, piston type, shared module type, shared wall type, etc.), electro-thermal conversion methods (such as thermal inkjet type, BUBBLEJET (registered trademark) type, etc.), electrostatic attraction methods (such as electric field control type, slit jet type, etc.) and discharge methods (such as electric spark jet type, etc.). From the perspective of the cost and productivity of the inkjet head, it is preferred to use an inkjet head using an electro-mechanical conversion method or an electro-thermal conversion method. It should be noted that the method of dripping droplets (such as coating liquid) according to the inkjet method is sometimes called an "inkjet method".

[0205] The encapsulating composition is preferably applied under a nitrogen atmosphere.

[0206] (Reforming process)

[0207] The modification step may include a step of modifying the obtained coating film by irradiating it with vacuum ultraviolet rays in a nitrogen atmosphere after the coating step.

[0208] The modification treatment refers to a conversion reaction of polysilazane into silicon oxide or silicon oxynitride. The modification treatment is also performed in a nitrogen atmosphere and under reduced pressure in a glove box.

[0209] The modification treatment in the present invention can be selected from a known method based on the conversion reaction of polysilazane. In the present invention, it is preferred to use a conversion reaction of plasma, ozone, or ultraviolet light that can perform the conversion reaction at low temperature. Plasma and ozone can use a conventionally known method. In the present invention, it is preferred to form the second encapsulation layer of the present invention by providing the above-mentioned coating film and irradiating vacuum ultraviolet light (also referred to as VUV) with a wavelength of less than 200nm for modification treatment.

[0210] The thickness of the second encapsulating layer is preferably in the range of 0.5 to 20 μm, more preferably in the range of 3 to 10 μm.

[0211] The second encapsulating layer may be a layer whose entire layer is modified, and the thickness of the modified layer after the modification treatment is preferably in the range of 1 to 50 nm, and more preferably in the range of 1 to 30 nm.

[0212] In the step of irradiating the coating film with vacuum ultraviolet rays for modification, the illuminance of the vacuum ultraviolet rays on the coating film surface is preferably 30 to 200 mW / cm 2 The range of 50 to 160 mW / cm 2 By making the illuminance of vacuum ultraviolet light 30mW / cm 2 Above, the reforming efficiency can be fully improved, at 200mW / cm 2 When the ratio is less than 0.1, the occurrence rate of damage to the coating film can be extremely suppressed, and damage to the substrate can also be reduced, which is preferred.

[0213] The irradiation energy of vacuum ultraviolet rays on the coating film surface is preferably 1 to 10 J / cm 2 In the range of 3 to 7 J / cm2, from the viewpoint of the barrier property and moisture heat resistance for maintaining the dehumidification function, the 2 within the range.

[0214] It should be noted that as the light source of vacuum ultraviolet light, it is preferred to use a rare gas excimer lamp. Since vacuum ultraviolet light is due to the absorption based on oxygen, the efficiency in the vacuum ultraviolet light irradiation process is easily reduced, so the irradiation of vacuum ultraviolet light is preferably carried out under a low oxygen concentration as much as possible. That is, the oxygen concentration during vacuum ultraviolet light irradiation is preferably in the range of 10 to 10000ppm, more preferably in the range of 50 to 5000ppm, further preferably in the range of 80 to 4500ppm, and most preferably in the range of 100 to 1000ppm.

[0215] The modification treatment may also be combined with the heat treatment. By using the heat treatment preferably at a temperature in the range of 50 to 300° C., more preferably in the range of 60 to 150° C., for preferably 1 second to 60 minutes, more preferably 10 seconds to 10 minutes as the heating condition, the dehydration condensation reaction during the modification can be promoted, and the modified body can be formed more effectively.

[0216] As the heat treatment, for example, there can be mentioned a method of heating the coating film by heat conduction by bringing the substrate into contact with a heating body such as a heating block, a method of heating the atmosphere by using an external heater based on a resistance wire, etc., a method of using light in the infrared region such as an IR heater, etc., without particular limitation. In addition, a method that can maintain the smoothness of the coating film containing the silicon compound can be appropriately selected.

[0217] <Third Encapsulation Layer Formation Step>

[0218] The third encapsulation layer forming step forms a third encapsulation layer on the second encapsulation layer by a vapor phase method.

[0219] As the gas phase method, similar to the gas phase method used in the first encapsulation layer forming step, there can be mentioned a sputtering method (for example, reactive sputtering methods including magnetron cathode sputtering, planar magnetron sputtering, dipole AC planar magnetron sputtering, dipole AC rotating magnetron sputtering, etc.), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), a thermal CVD method, a catalytic chemical vapor deposition method (Cat-CVD), a capacitively coupled plasma CVD method (CCP-CVD), a photo CVD method, a plasma CVD method (PE-CVD), an epitaxial growth method, a chemical vapor deposition method such as an atomic layer deposition method (ALD), etc. Among them, formation by an ALD method or a CVD method is preferred.

[0220] The third encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).

[0221] As a specific example of forming the third encapsulation layer, the following method can be cited: the pressure in the chamber is reduced in advance, silane (SiH 4 ), ammonia (NH 3 ), hydrogen (H 2 ) is formed by heating the raw material gas and supplying it into the chamber.

[0222] The thickness of the third encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.

[0223] It should be noted that after the package film is formed as described above, a conductive film for a touch sensor may be further formed.

[0224] The conductive film may be composed of a graphene film having excellent flexibility, a metal nanowire film (e.g., a film containing silver nanowires or copper nanowires), or a metal nanoparticle film (e.g., a film containing silver nanoparticles or copper nanoparticles), in addition to a metal compound film such as ITO (Indium Tin Oxide) or IZO (Indium Zinc Oxide). In addition, the conductive film may be composed of a laminated film of multiple metals such as Al film / Ti film / Al film.

[0225] [Electronic device packaging film]

[0226] An electronic device encapsulating film according to one embodiment of the present invention is an electronic device encapsulating film obtained by curing an electronic device encapsulating composition containing a photopolymerizable monomer and a photopolymerization initiator to encapsulate an electronic device, wherein the electronic device encapsulating film contains a (meth)acrylate as the photopolymerizable monomer, and the refractive index of the electronic device encapsulating film at a wavelength of 380 nm is within a range of 1.45 to 1.56, and the extinction coefficient of the electronic device encapsulating film at a wavelength of 380 nm is within a range of 50×10 -5 ~200×10 -5 within the range.

[0227] Another embodiment of the present invention is an electronic device encapsulating film for encapsulating an electronic device, comprising a first encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride, and a second encapsulating layer formed using the electronic device encapsulating composition of the present invention.

[0228] Such an electronic device encapsulating film of the present invention is formed by the above-mentioned method for forming an electronic device encapsulating film. That is, the second encapsulating layer is formed using the above-mentioned composition for encapsulating an electronic device of the present invention.

[0229] The refractive index of the second encapsulation layer at a wavelength of 380 nm is in the range of 1.45 to 1.56, and the extinction coefficient at a wavelength of 380 nm is in the range of 50×10 -5 ~200×10 -5 within the range.

[0230] In addition, the electronic device encapsulating film of the present invention preferably further comprises a third encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulating layer.

[0231] <1st packaging layer>

[0232] The first encapsulation layer is a layer formed on the electronic device by the above-mentioned vapor phase method, and specifically contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.), or silicon oxynitride.

[0233] <Second Encapsulation Layer>

[0234] The second encapsulating layer is provided adjacent to the first encapsulating layer, and is formed by applying the encapsulating composition on the first encapsulating layer.

[0235] Therefore, the second encapsulating layer contains a polymer composed of the specific photopolymerizable monomer contained in the encapsulating composition.

[0236] As a method for detecting that the second encapsulation layer contains the polymer, various conventionally known analytical methods can be used, such as chromatography, infrared spectroscopy, ultraviolet / visible spectroscopy, nuclear magnetic resonance analysis, X-ray diffraction and mass spectrometry, X-ray photoelectron spectroscopy, etc.

[0237] The content of the polymer in the second encapsulating layer is preferably in the range of 85 to 100% by mass, more preferably in the range of 90 to 95% by mass.

[0238] <Third Encapsulation Layer>

[0239] The third encapsulation layer is provided adjacent to the second encapsulation layer and is formed by the vapor phase method, and specifically, contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.), or silicon oxynitride, similarly to the first encapsulation layer.

[0240] [Electronic devices]

[0241] In the method for forming an electronic device encapsulation film and the electronic device encapsulation film of the present invention, the encapsulated electronic device may be, for example, an organic EL element, an LED element, a liquid crystal display element (LCD), a thin film transistor, a touch panel, an electronic paper, a solar cell (PV), etc. From the viewpoint of more effectively obtaining the effect of the present invention, an organic EL element, a solar cell or an LED element is preferred, and an organic EL element is particularly preferred.

[0242] <Organic EL devices>

[0243] The organic EL element used as the electronic device of the present invention may be a bottom emission type organic EL element, that is, an organic EL element that extracts light from the transparent substrate side.

[0244] Specifically, the bottom emission type is constituted by laminating a transparent electrode as a cathode, a light-emitting functional layer, and a counter electrode as an anode in this order on a transparent substrate.

[0245] The organic EL element of the present invention may be a top emission type, that is, an organic EL element that extracts light from a transparent electrode side serving as a cathode opposite to a substrate.

[0246] Specifically, the top emission type has a structure in which a counter electrode as an anode is provided on the substrate side, and a light-emitting functional layer and a transparent electrode as a cathode are sequentially stacked on the surface thereof.

[0247] A typical example of the structure of an organic EL element is shown below.

[0248] (i) Anode / Hole injection and transport layer / Emitting layer / Electron injection and transport layer / Cathode

[0249] (ii) Anode / hole injection and transport layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode

[0250] (iii) Anode / hole injection and transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode

[0251] (iv) Anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / cathode

[0252] (v) Anode / hole injection layer / hole transport layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode

[0253] (vi) anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode

[0254] Furthermore, the organic EL element may have a non-luminescent intermediate layer. The intermediate layer may be a charge generating layer or may be composed of a multiphoton unit.

[0255] As for the outline of the organic EL element applicable to the present invention, for example, Japanese Patent Application Laid-Open No. 2013-157634, Japanese Patent Application Laid-Open No. 2013-168552, Japanese Patent Application Laid-Open No. 2013-177361, Japanese Patent Application Laid-Open No. 2013-187211, Japanese Patent Application Laid-Open No. 2013-191644, Japanese Patent Application Laid-Open No. 2013-191804, Japanese Patent Application Laid-Open No. 2013-225678, Japanese Patent Application Laid-Open No. 2013-235994, Japanese Patent Application Laid-Open No. 2013-2 The configurations described in Japanese Patent Application Laid-Open No. 43234, Japanese Patent Application Laid-Open No. 2013-243236, Japanese Patent Application Laid-Open No. 2013-242366, Japanese Patent Application Laid-Open No. 2013-243371, Japanese Patent Application Laid-Open No. 2013-245179, Japanese Patent Application Laid-Open No. 2014-003249, Japanese Patent Application Laid-Open No. 2014-003299, Japanese Patent Application Laid-Open No. 2014-013910, Japanese Patent Application Laid-Open No. 2014-017493, Japanese Patent Application Laid-Open No. 2014-017494, etc.

[0256] <Base material>

[0257] As a substrate (hereinafter also referred to as a supporting substrate, base, substrate, support, etc.) that can be used for the above-mentioned organic EL element, specifically, glass or a resin film is preferably used. When flexibility is required, a resin film is preferably used.

[0258] In addition, it may be transparent or opaque. In the case of a so-called bottom emission type in which light is extracted from the substrate side, the substrate is preferably transparent.

[0259] Preferred resins include polyester resins, methacrylic resins, methacrylic acid-maleic acid copolymers, polystyrene resins, transparent fluorine resins, polyimides, fluorinated polyimide resins, polyamide resins, polyamide-imide resins, polyether-imide resins, cellulose acylate resins, polyurethane resins, polyether-ether-ketone resins, polycarbonate resins, alicyclic polyolefin resins, polyarylate resins, polyethersulfone resins, polysulfone resins, cycloolefin copolymers, fluorene ring-modified polycarbonate resins, alicyclic-modified polycarbonate resins, fluorene ring-modified polyester resins, acrylic compounds and other thermoplastic resins. The resins may be used alone or in combination of two or more.

[0260] The substrate is preferably made of a heat-resistant material. Specifically, a substrate having a linear expansion coefficient of 15 ppm / K to 100 ppm / K and a glass transition temperature (Tg) of 100°C to 300°C is used.

[0261] The substrate meets the necessary conditions for use in electronic components and as a laminated film for displays. That is, when the encapsulation film of the present invention is used in these applications, the substrate is sometimes exposed to a process above 150°C. In this case, if the linear expansion coefficient of the substrate exceeds 100ppm / K, the substrate size is unstable when flowing through the process at the temperature described above, and it is easy to produce the undesirable situation of deterioration of the blocking performance or the undesirable situation of being unable to withstand the thermal process due to thermal expansion and contraction. When it is less than 15ppm / K, the film will break like glass, and there is a situation of deterioration of flexibility.

[0262] The Tg and linear expansion coefficient of the substrate can be adjusted by additives and the like.

[0263] More preferred specific examples of thermoplastic resins that can be used as the substrate include polyethylene terephthalate (PET: 70°C), polyethylene naphthalate (PEN: 120°C), polycarbonate (PC: 140°C), alicyclic polyolefins (e.g., ZEONOR (registered trademark) 1600 manufactured by Zeon Corporation: 160°C), polyarylate (PAr: 210°C), polyether sulfone (PES: 220°C), polysulfone (PSF: 190°C), cycloolefin copolymer (COC: described in Japanese Patent Application Laid-Open No. 2001-150584) and polyether sulfone (PES: 220°C). Compounds: 162°C), polyimides (e.g., Neopulim (registered trademark) manufactured by Mitsubishi Gas Chemical Co., Ltd.: 260°C), fluorene ring-modified polycarbonate (BCF-PC: compounds described in JP-A-2000-227603: 225°C), alicyclic modified polycarbonate (IP-PC: compounds described in JP-A-2000-227603: 205°C), acrylic compounds (compounds described in JP-A-2002-80616: 300°C or more), etc. (temperatures in parentheses represent Tg).

[0264] The electronic device of the present invention is an electronic device such as an organic EL element, so the substrate is preferably transparent. That is, the light transmittance is usually 80% or more, preferably 85% or more, and more preferably 90% or more. The light transmittance can be measured by the method described in JIS K7105: 1981, that is, an integrating sphere light transmittance measuring device to measure the total light transmittance and the amount of scattered light, and calculated by subtracting the diffuse transmittance from the total light transmittance.

[0265] In addition, the substrates mentioned above can be unstretched films or stretched films. The substrates can be manufactured by conventional methods known in the past. Regarding the manufacturing methods of these substrates, the matters described in paragraphs "0051" to "0055" of International Publication No. 2013 / 002026 can be appropriately adopted.

[0266] The surface of the substrate may be subjected to various known treatments for improving adhesion, such as corona discharge treatment, flame treatment, oxidation treatment or plasma treatment, or the above treatments may be combined as required. In addition, the substrate may be subjected to an easy-adhesion treatment.

[0267] The substrate may be a single layer or a laminated structure of two or more layers. When the substrate has a laminated structure of two or more layers, each substrate may be of the same type or of different types.

[0268] The thickness of the substrate of the present invention (the total thickness in the case of a laminated structure of two or more layers) is preferably 10 to 200 μm, more preferably 20 to 150 μm.

[0269] In the case of a film substrate, a film substrate with a gas barrier layer is preferred.

[0270] The gas barrier layer for the film substrate may be formed as an inorganic film, an organic film or a mixed film of the two on the surface of the film substrate, and preferably has a water vapor permeability (25±0.5°C, relative humidity (90±2)%RH) of 0.01 g / m 2 The barrier film with a shelf life of 24 hours or less is more preferably an oxygen permeability of 1×10 -3 mL / m 2 ·24h·atm or less, water vapor transmission rate is 1×10 - 3 g / m 2 ·High gas barrier film for less than 24 hours.

[0271] The gas barrier layer may be formed of any material as long as it has the function of suppressing the infiltration of substances such as moisture and oxygen that cause element degradation, and for example, silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, silicon oxycarbide, etc. can be used.

[0272] The gas barrier layer is not particularly limited. For example, in the case of an inorganic gas barrier layer of silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, silicon oxycarbide, etc., it is preferred to form a layer using a chemical vapor deposition method such as sputtering (for example, magnetron cathode sputtering, planar magnetron sputtering, diode AC planar magnetron sputtering, diode AC rotary magnetron sputtering, etc.), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), thermal CVD, catalytic chemical vapor deposition (Cat-CVD), capacitively coupled plasma CVD (CCP-CVD), photo CVD, plasma CVD (PE-CVD), epitaxial growth, atomic layer deposition (ALD) method, reactive sputtering, etc.

[0273] Furthermore, the inorganic gas barrier layer can also be formed by coating a coating liquid containing an inorganic precursor such as polysilazane, tetraethyl orthosilicate (TEOS) on a support and then performing a modification treatment such as irradiation with vacuum ultraviolet light to form an inorganic gas barrier layer, or by thin-film metallization techniques such as plating a metal on a resin substrate to bond a metal foil to the resin substrate.

[0274] In addition, the inorganic gas barrier layer may include an organic layer containing an organic polymer. In other words, the inorganic gas barrier layer may be a laminate of an inorganic layer containing an inorganic material and an organic layer.

[0275] The organic layer can be formed, for example, by coating an organic monomer or an organic oligomer on a resin substrate to form a layer, followed by polymerization and crosslinking as required using, for example, an electron beam device, a UV light source, a discharge device or other appropriate device. Alternatively, it can be formed, for example, by evaporating an organic monomer or an organic oligomer that can flash evaporate and crosslink with radiation, and then forming a polymer from the organic monomer or organic oligomer. The coating efficiency can be improved by cooling the resin substrate.

[0276] As the coating method of organic monomer or organic oligomer, for example, roll coating (for example gravure roll coating), spray coating (for example electrostatic spray coating) etc. can be enumerated. In addition, as the example of the laminate of inorganic layer and organic layer, for example, the laminate of record in International Publication No. 2012 / 003198 and International Publication No. 2011 / 013341 etc. can be enumerated.

[0277] In the case of a laminate of an inorganic layer and an organic layer, the thickness of each layer may be the same or different. The thickness of the inorganic layer is preferably in the range of 3 to 1000 nm, more preferably in the range of 10 to 300 nm. The thickness of the organic layer is preferably in the range of 100 nm to 100 μm, more preferably in the range of 1 to 50 μm.

[0278] Example

[0279] The present invention is specifically described below with reference to examples, but the present invention is not limited thereto. It should be noted that in the following examples, unless otherwise specified, the operation is performed at room temperature (25° C.). In addition, unless otherwise specified, “%” and “parts” represent “mass %” and “mass parts”, respectively.

[0280] [monomer]

[0281] The monomers used to prepare the encapsulating composition are as follows. The HOMO and LUMO values ​​of each monomer were calculated by the method described below and are shown in Table I below. The refractive index (nd25) of the D line at 25° C. was calculated for each monomer using an Abbe refractometer and is shown in Table I below.

[0282]

[0283]

[0284]

[0285] [Table 1]

[0286] Table I

[0287] Monomer number Compound Name HOMO[eV] LUMO[eV] Refractive index n a002 Triethylene glycol diacrylate -6.8 -1.3 1.46 a008 Triethylene glycol dimethacrylate -7.0 -1.2 1.46 a010 Isoamyl acrylate -7.5 -1.2 1.42 a016 Dipropylene glycol diacrylate -6.9 -0.9 1.45 a017 Tripropylene glycol diacrylate -6.9 -1.2 1.45 a026 TMPTA trimethylolpropane triacrylate -7.5 -1.3 1.47 a036 1,4-Butanediol diacrylate -7.6 -1.2 1.45 a037 1,6-Hexanediol diacrylate -7.5 -1.2 1.46 a039 Neopentyl glycol diacrylate -7.6 -1.2 1.46 a041 2-Methyl-1,8-octanediol diacrylate -7.3 -1.2 1.46 a042 1,10-Decanediol diacrylate -7.4 -1.2 1.46 a043 Cyclohexanedimethanol diacrylate -7.3 -1.2 1.47 a044 Tricyclodecane dimethanol diacrylate -7.3 -1.2 1.48 a076 Dicyclopentyl acrylate -7.2 -1.2 1.50 a079 2-Ethylhexyl acrylate -7.3 -1.2 1.44 a081 Lauryl acrylate -7.4 -1.2 1.44 a084 Isobornyl acrylate -7.0 -1.1 1.48 a087 Rosin Acrylate -6.1 -1.3 1.49 a107 N,N'-ethylenebisacrylamide -6.6 -1.1 1.47 a112 Ethoxylated o-phenylphenol acrylate -6.0 -1.3 1.58 a119 9,9-Bis(4-(2-acryloyloxyethoxy)phenyl)fluorene -6.0 -1.3 1.54 a121 Benzyl acrylate -6.7 -1.2 1.52 a122 2-Phenoxyethyl acrylate -6.2 -1.3 1.52 a129 Cyclohexyl methacrylate -7.3 -1.1 1.46 a130 Benzyl methacrylate -6.7 -1.1 1.51 a133 2-Phenoxyethyl Methacrylate -6.2 -1.2 1.51 a134 1,12-Dodecanediol dimethacrylate -7.3 -1.0 1.46 a136 Isodecyl acrylate -7.5 -1.2 1.45 a139 Dicyclopentyl methacrylate -7.3 -1.0 1.45 a140 Dodecyl acrylate -7.4 -1.2 1.45 a143 2-(4-Nonylphenoxy)ethyl prop-2-enoate -5.9 -1.3 1.49 a147 2-(2-Naphthyloxy)ethyl acrylate) -6.0 -1.3 1.52

[0288] [Preparation of Encapsulating Compositions 1 to 28]

[0289] Each monomer was weighed under a nitrogen atmosphere so as to have the type and mass fraction shown in Table II below.

[0290] Furthermore, 5 parts by mass of a phosphorus-based initiator (Omnirad 819 manufactured by IGM) as a photopolymerization initiator and 0.5 parts by mass of 2-isopropylthioxanthone (manufactured by Merck) as a sensitizer were placed in a brown bottle and stirred on a hot plate at 65° C. for 3 hours to obtain encapsulating compositions 1 to 28.

[0291] [Table 2]

[0292] Table II

[0293]

[0294] [Refractive index n and extinction coefficient k]

[0295] In a nitrogen environment, a coating film of the encapsulation composition was formed on a glass substrate having a size of 50 mm×50 mm to a thickness of 100 nm. The coating film was heated at 300 mW / cm 2 The accumulated light intensity under the condition is 1.5J / cm 2 The coating was cured by irradiating with ultraviolet light of 395 nm wavelength (MZ 240mm 395nm UVLED manufactured by IST) to prepare a measurement sample. The refractive index and extinction coefficient of the measurement sample at 250 nm to 800 nm were measured using a UVSEL / FUV-FGMS spectroscopic ellipsometer manufactured by HORIBA JYOBIN-YVON, and the refractive index n at 380 nm and the extinction coefficient k at 380 nm of the cured film of the encapsulation composition were calculated and shown in the following Table III.

[0296] Furthermore, the ratio k / n of the extinction coefficient k at 380 nm to the refractive index n at 380 nm was determined and shown in the following Table III.

[0297] [Average number of double bonds]

[0298] The average number of double bonds was calculated as follows using the mass ratio w of each monomer when the number of double bonds contained in each monomer is defined as d and the total mass of all monomers is defined as 1, and is shown in the following Table III.

[0299] Average number of double bonds = d1×w1+d2×w2+···

[0300] (The subscripts d and w indicate the monomer numbers.)

[0301] [Energy levels of HOMO and LUMO]

[0302] The HOMO and LUMO (unit: eV) of each monomer were obtained using Gaussian software manufactured by HULINKS based on the information of the chemical structure. In the calculation, B3LYP was used as a functional. The HOMO and LUMO values ​​of each monomer are shown in Table II. The average value of HOMO and the average value of LUMO were calculated based on the values ​​of HOMO and LUMO of each monomer obtained by the following formula, and the energy gap (Gap) was calculated based on the average value of HOMO and the average value of LUMO, which is shown in Table III below.

[0303] Average value of HOMO = HOMO1×w1+HOMO2×w2+...

[0304] Average value of LUMO = LUMO1×w1+LUMO2×w2+...

[0305] In the above formula, w represents the mass ratio of each monomer. In addition, the subscripts of w, HOMO and LUMO represent the monomer numbers.

[0306] Gap (unit: eV) = average value of LUMO - average value of HOMO

[0307] [Production of organic EL elements]

[0308] (1) Preparation of substrate

[0309] A 15 μm thick polyimide film was prepared as a film substrate. A gas barrier layer (SiO 2 Film: 250nm / SiNx Film: 50nm / SiO 2 Membrane: 500nm (upper layer / middle layer / lower layer)).

[0310] (2) Formation of the first electrode

[0311] An Al film was formed as a first electrode (metal layer) on one surface of the substrate under the following conditions. The thickness of the formed first electrode was 150 nm. It should be noted that the thickness of the first electrode is a value measured using a contact surface profile measuring instrument (DECTAK).

[0312] The Al film was deposited using a vacuum evaporation device with a vacuum pressure of 1×10 -4 Pa and then formed using a tungsten resistance heating crucible.

[0313] (3) Formation of organic EL layer

[0314] First, each evaporation crucible in a vacuum evaporation device is filled with the following materials constituting each layer of the organic functional layer in an amount optimal for producing each element. The evaporation crucible is made of a resistance heating material made of molybdenum or tungsten.

[0315] (3-1) Formation of Hole Injection Layer

[0316] Reduce the pressure to a vacuum degree of 1×10 -4 After Pa, the crucible for vapor deposition containing the following compound A-1 was energized and heated, and vapor-deposited onto the first electrode (metal layer side) at a vapor deposition rate of 0.1 nm / sec to form a hole injection layer with a thickness of 10 nm.

[0317] (3-2) Formation of hole transport layer

[0318] Next, the following compound M-2 was placed in a deposition crucible, which was energized and heated, and was deposited on the hole injection layer at a deposition rate of 0.1 nm / sec to form a hole transport layer with a thickness of 30 nm.

[0319] (3-3) Formation of Light Emitting Layer

[0320] Next, the following compound BD-1 and the following compound H-1 were co-deposited at a deposition rate of 0.1 nm / sec so that the concentration of compound BD-1 was 7 mass %, thereby forming a 15 nm thick light-emitting layer (fluorescent light-emitting layer) that emitted blue light.

[0321] Next, the following compounds GD-1, RD-1 and H-2 were co-deposited at a deposition rate of 0.1 nm / sec so that the concentrations of GD-1 and RD-1 were 20% by mass and 0.5% by mass, respectively, to form a yellow light-emitting layer (phosphorescent light-emitting layer) having a thickness of 15 nm.

[0322] (3-4) Formation of electron transport layer

[0323] Then, the heating boat containing the following compound T-1 as an electron transport material was energized to form a light emitting layer composed of Alq 3 The electron transport layer is composed of (tris(8-hydroxyquinoline)). At this time, the vapor deposition rate is set in the range of 0.1 to 0.2 nm / sec, and the thickness is set to 30 nm.

[0324] (3-5) Formation of electron injection layer (metal affinity layer)

[0325] Next, the heating boat containing the following compound I-1 as an electron injection material was energized and heated to form an electron injection layer composed of Liq on the electron transport layer. At this time, the evaporation rate was set within the range of 0.01 to 0.02 nm / sec, and the thickness was set to 2 nm. It should be noted that the electron injection layer functions as a metal affinity layer.

[0326] Thereby, an organic EL layer emitting white light is formed.

[0327]

[0328] (4) Formation of the Second Electrode

[0329] Furthermore, a Mg / Ag mixture (Mg:Ag=1:9 (vol ratio)) was vapor-deposited to a thickness of 10 nm to form an extraction electrode as a second electrode.

[0330] (5) Formation of the covering layer

[0331] Then, it was transferred to the original vacuum chamber, and α-NPD (4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl) was vapor-deposited on the second electrode at a vapor deposition rate of 0.1 to 0.2 nm / sec until the thickness reached 40 nm, forming a covering layer for the purpose of improving light extraction.

[0332] (6) Formation of the first encapsulation layer

[0333] Next, as a first sealing layer covering the light-emitting portion of the organic EL element produced above, silicon nitride (SiNx, Vickers hardness HV900) was formed to a thickness of 500 nm by a plasma CVD method.

[0334] (7) Formation of the Second Encapsulation Layer

[0335] Next, the encapsulation composition 1 prepared above was filled into an inkjet head (KM1024i-MHE-D manufactured by Konica Minolta) under a nitrogen environment. Then, the encapsulation composition 1 was applied to the organic EL element formed up to the first encapsulation layer under a nitrogen environment using an inkjet method in a coating thickness of 10 μm. Then, the encapsulation composition 1 was applied at 300 mW / cm 2 The accumulated light intensity under the condition is 1.5J / cm 2 The second encapsulation layer is formed by irradiating ultraviolet light with a wavelength of 395 nm (MZ 240 mm 395 nm UV LED manufactured by IST).

[0336] (8) Formation of the third encapsulation layer

[0337] Next, silicon nitride (SiNx, Vickers hardness HV900) was formed as a third encapsulating layer with a thickness of 500 nm on the second encapsulating layer by plasma CVD, thereby obtaining an organic EL element 1 for evaluation having the first to third encapsulating layers formed thereon.

[0338] [Production of Organic EL Elements 2 to 28]

[0339] In the production of the organic EL element 1, organic EL elements 2 to 28 for evaluation were produced in the same manner except that the encapsulating composition 1 in the formation of the second encapsulating layer was changed as shown in the following table.

[0340] [evaluate]

[0341] <Reliability test after bending (luminous efficiency)>

[0342] The obtained sample of the organic EL element for evaluation was made to emit light, and the luminous efficiency (unit: lm / W) was measured as the initial luminous efficiency. Then, the evaluation sample was repeatedly bent 200,000 times at a bending radius of R = 2.5 mm at room temperature using a clamshell-type repeated bending tester (Tension-Free(R) Folding Clamshell-type table-type durability tester manufactured by YUASA). Then, the luminous efficiency (unit: lm / W) of the evaluation sample was measured as the luminous efficiency after bending.

[0343] The change rate (%) of the luminous efficiency after bending relative to the initial luminous efficiency was evaluated and judged according to the following evaluation criteria. Levels 2 to 4 were evaluated as acceptable.

[0344] (Evaluation Criteria)

[0345] Level 1: Less than 80%

[0346] Level 2: 80% or more and less than 90%

[0347] Level 3: 90% or more and less than 95%

[0348] Level 4: 95% or more

[0349] <Crease after bending (evaluation of film deformation after folding resistance test)>

[0350] A 15 μm thick polyimide film was prepared as a film substrate, and a sealing layer was formed on the polyimide film by the same method as (6) Formation of the first sealing layer, (7) Formation of the second sealing layer, and (8) Formation of the third sealing layer to prepare an evaluation sample.

[0351] Bend the evaluation sample with a bending radius of R = 2.0 mm in a way that the polyimide film side is convex. Fix it in the bent state and keep it in an environment of 85°C for 72 hours. Take out the evaluation sample and measure the surface shape profile of the third packaging layer side using a contact film thickness meter (Bruker dektak XT). In the case of film deformation, observe the concave and convex shapes, evaluate the maximum height of the convex shape and the maximum depth of the concave shape, and judge according to the following evaluation criteria. Grades 2 to 4 are rated as qualified.

[0352] (Evaluation Criteria)

[0353] Level 1: Maximum height or maximum depth is 5 μm or more

[0354] Level 2: Maximum height or maximum depth is 3 μm or more and less than 5 μm

[0355] Level 3: Maximum height or maximum depth is 1 μm or more and less than 3 μm

[0356] Level 4: Maximum height or maximum depth is less than 1 μm

[0357] <Relative dielectric constant>

[0358] In a nitrogen environment, a coating film of the encapsulating composition having a thickness of 50 μm was prepared on a releasable film substrate having a size of 100 mm×100 mm. The coating film was heated at 300 mW / cm 2 The accumulated light intensity under the condition is 1.5mJ / cm 2 The coating film is cured by irradiating ultraviolet rays of a wavelength of 395nm (MZ 240mm 395nm UVLED made by IST company). The cured film obtained is peeled off from the release film, and then a Ag film is formed on both sides by sputtering to make a measurement sample. The measurement sample is measured by impedance measurement device (Solartron 126096) with a frequency of 100kHz and AC 0.1 (V) to measure the relative dielectric constant. It is qualified to be less than 2.9, and it is unqualified to be more than 2.9.

[0359] [Table 3]

[0360] Table III

[0361]

[0362] As shown in the above results, it can be seen that the encapsulating composition of the present invention can obtain an encapsulating film having good appearance after the reliability test in a folded state, excellent luminous efficiency after the folding reliability test, and low relative dielectric constant, compared with the encapsulating composition of the comparative example.

[0363] Industrial Applicability

[0364] The present invention can be used for an electronic device encapsulation composition, an electronic device encapsulation film, and a method for forming an electronic device encapsulation film, which can obtain an encapsulation film having good appearance after a reliability test in a folded state, excellent luminous efficiency after a folded reliability test, and a low relative dielectric constant.

Claims

1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator, Contains (meth)acrylate as a photopolymerizable monomer, In nitrogen environment, 1.5 J cm -2 When cured by irradiation with ultraviolet light of wavelength 395 nm, the refractive index of the formed electronic device packaging film at wavelength 380 nm is in the range of 1.45 to 1.56, and the extinction coefficient of the electronic device packaging film at wavelength 380 nm is within the range of 50×10 -5 ~200×10 -5 within the range.

2. The composition for electronic device encapsulation according to claim 1, wherein The refractive index is in the range of 1.50 to 1.

53.

3. The composition for electronic device encapsulation according to claim 1, wherein The extinction coefficient is 125×10 -5 ~200×10 -5 within the range.

4. The composition for electronic device encapsulation according to claim 1, wherein The refractive index n and the extinction coefficient k satisfy the following relationship, k / n≥100×10 -5 。 5. The composition for electronic device encapsulation according to claim 1, wherein The photopolymerizable monomer contained in the composition for encapsulating electronic components has an average double bond number of 5 or less.

6. The composition for encapsulating electronic devices according to claim 1, wherein The energy levels of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the photopolymerizable monomer contained in the composition for encapsulating electronic devices satisfy the following relationship: 5.9eV≤LUMO-HOMO≤6.5eV.

7. An electronic device encapsulating film, which is an electronic device encapsulating film obtained by encapsulating an electronic device by curing a composition for encapsulating an electronic device containing a photopolymerizable monomer and a photopolymerization initiator, contains (meth)acrylate as the photopolymerizable monomer, The refractive index of the electronic device packaging film at a wavelength of 380 nm is in the range of 1.45 to 1.56, and The extinction coefficient of the electronic device packaging film at a wavelength of 380nm is 50×10 -5 ~200×10 -5 within the range.

8. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having: The first encapsulation layer comprises silicon nitride, silicon oxide or silicon oxynitride, and The second encapsulating layer uses the composition for encapsulating an electronic device according to any one of claims 1 to 6.

9. The electronic device packaging film according to claim 8, wherein: A third encapsulation layer including silicon nitride, silicon oxide or silicon oxynitride is provided on the second encapsulation layer.

10. A method for forming an electronic device encapsulating film, comprising forming an electronic device encapsulating film using the composition for encapsulating an electronic device according to any one of claims 1 to 6, the method comprising: The process of forming a first encapsulation layer on the electronic device by a vapor phase method, and A step of forming a second encapsulating layer by applying the electronic device encapsulating composition on the first encapsulating layer.

11. The method for forming an electronic device packaging film according to claim 10, wherein: The method comprises the step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.

12. The method for forming an electronic device packaging film according to claim 10, wherein: The second encapsulation layer is formed by an inkjet method.